2012
DOI: 10.1016/j.ijgo.2012.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum hemorrhage management in 2012: Predicting the future

Abstract: Transfusion therapy in postpartum hemorrhage (PPH) traditionally has been modeled after precedents set in the Vietnam and Korean wars. However, data from recent military combat casualties suggest a different transfusion strategy. Transfusion of packed red blood cells, fresh frozen plasma, and platelets in a ratio of 1:1:1 improves dilutional coagulopathy and survival. Women who present with low fibrinogen at the time of diagnosis of PPH have poorer outcomes and might benefit from early fibrinogen replacement. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 25 publications
0
24
0
3
Order By: Relevance
“…(12) Studies on the use of MTPs in non-trauma settings are lacking and limited to gastrointestinal tract and major obstetric haemorrhages. (12,13) Thus, the aim of the present study was to assess the efficacy and outcomes of a newly established MTP that was used in an acute surgical care unit for both trauma and non-trauma surgical patients.…”
Section: Introductionmentioning
confidence: 99%
“…(12) Studies on the use of MTPs in non-trauma settings are lacking and limited to gastrointestinal tract and major obstetric haemorrhages. (12,13) Thus, the aim of the present study was to assess the efficacy and outcomes of a newly established MTP that was used in an acute surgical care unit for both trauma and non-trauma surgical patients.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors suggest that fixed-ratio platelet transfusion is an appropriate strategy during severe postpartum haemorrhage [17,18,20]. In our cohort we estimate that, if fixedratio transfusion had been used, multiple platelets would have been given to women with platelets counts well above those recommended in guidelines and women with clinically significant thrombocytopenia would not have received platelets.…”
Section: Discussionmentioning
confidence: 91%
“…There is a trend to adopt fixed-ratio platelet transfusion in postpartum haemorrhage [12,[17][18][19][20], a practice directly extrapolated from major trauma [21] despite the coagulopathies of trauma and obstetric bleeding being markedly different [5][6][7][22][23][24]. No studies have investigated whether this is an appropriate or safe strategy, and some groups describe good outcomes with low rates of platelet transfusion [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed the Carbetocin, similarly to Oxytocin, it causes an increase in the intracellular concentration of calcium that promotes uterine contractility, through the generation of inositol phosphatas [24]. This evidence, associated to haemodynamic safety profile [14], they are important results in the attempt to define a more comprehensive assessment and possibility of application. Indeed preeclampsia and eclampsia are contraindications to the administration of Carbetocin currently, but the evidence of lack of prothrombotic effect suggest a new threshold in the attempt to enlarge the therapy indications.…”
Section: Discussionmentioning
confidence: 99%
“…Also, our research group in a recent study demonstrated that a single injection of Carbetocin has more effective than a continuous infusion of Oxytocin to maintain adequate uterine tone, with a similar safety profile and minor antidiuretic effect, and a very good haemodynamic profile [14].…”
Section: Introductionmentioning
confidence: 97%